Leveraging Digital Transformation for Enhanced ESG Performance - Csiszár, Csilla Margit; Hódiné Hernádi, Bettina (Észak-magyarországi Stratégiai Füzetek, 2024)
Digital transformation plays an important role in achieving ESG (environmental, social and governance) goals, as modern technologies support sustainability efforts. Digital tools such as cloud computing, smart robotics and IoT enable companies to manage their resources more efficiently, reduce their environmental footprint and operate more transparently. The aim of this study is to explore how digitalisation contributes to the success of ESG strategies, in particular environmental sustainability, and how it helps companies to achieve their sustainability goals, focusing especially on Hungarian companies.